THE EFFECT OF TECHNICAL ANALYSIS ON INVESTMENT PROFIT (International Journal of Innovative Technologies in Economy, 2024)
The purpose of this study is to examine whether relying solely on technical analysis in investment does not greatly affect the profits to be obtained. The author is interested in this topic because most investors only use one type of analysis, wheter it’s technical or fundamental analysis before deciding to buy stocks. To carry out this research, a total of 8 stocks from different companies were taken in the transaction period in 2023 and using the SimInvest application from Sinarmas Sekuritas. The results show that relying on only one type of analysis can affect the profit earned, so it is important for investors to combine technical and fundamental analysis in every investment decision to get greater profit potential.